MEMANFAATKAN SUMBER DAYA ALAM SEKITAR: PENGOLAHAN NANAS MENJADI SUMBER POTENSI EKONOMI MASYARAKAT DESA TAMBAK MEKAR KECAMATAN JALAN CAGAK KABUPATEN SUBANG - Sahilan, Sahilan; Megawati, Devi; Rahayu, Marlina (STKIP Pesisir Selatan, 2025)
Transforming raw materials into processed products is key to creating higher economic value. Currently, most pineapple harvests are sold directly to middlemen, despite the fruit's immense potential for processing into a wide variety of products, from food and beverages to industrial raw materials. This research aims to explore the economic potential of pineapple processing as a natural resource utilization based on local wisdom. Pineapple is an agricultural commodity widely produced by rural communities, but its utilization has so far been limited to fresh consumption. Using a qualitative approach with a case study in one pineapple production center, this research explores various pineapple processing products, such as jam, chips, syrup, and preserves, that have added economic value. The results indicate that pineapple processing can significantly increase community income, create new jobs, and strengthen local economic resilience. Furthermore, this activity also reflects local wisdom practices that preserve natural resources. The research recommends the need for technological support, training, and market access to optimize the economic potential of pineapple processing.